Pengaruh Efikasi Diri dan Dukungan Sosial terhadap Stres Kerja Pegawai di Dinas Sosial Kabupaten Gowa - Maghfiratul Adewiah Dahlan; Chalid.Imran Musa; Rezky Amalia Hamka; Sitti Hasbiah; Widhi Nugraha Sumiharja Darmawinata (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study employed a quantitative approach with an associative research design. The population consisted of all employees of the Social Service Office of Gowa Regency, including both civil servants and non-civil servants, totaling 53 employees. The sampling technique used was total sampling (census), in which all members of the population were selected as research respondents. Data were collected through observation, interviews, questionnaires, and documentation. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. Model testing was conducted through the evaluation of the outer model and inner model to assess validity, reliability, and the relationships among research variables. The results showed that self-efficacy had a positive and significant effect on employee work stress at the Social Service Office of Gowa Regency. Meanwhile, social support did not have a significant effect on employee work stress. These findings indicate that self-efficacy is a factor that has a strong influence on the level of employee work stress, whereas social support has not been proven to significantly affect employee work stress at the Social Service Office of Gowa Regency.